The Current Development of Flipped Classroom Research Publications in Indonesia: A Bibliometric Mapping - Setyanto, Suroto Rosyd; Kartika, Tomy; Purnama, Ardian Pitra Satya (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
Due to the rapid spread of flipped classroom studies for the past few years, a literature study focusing on the trends and directions of its research become important. This article attempts to identify the current state and direction of Scopus-indexed publications regarding flipped classroom in Indonesia. Bibliometric analysis (Donthu et al., 2021) was utilized to examine 53 papers extracted from Scopus database that published from 2017 until 2023. By employing Harzing’s Publish or Perish and VOSviewer software, this study examined the trends in flipped classroom publication including the documents by year and citation structure, prolific author, most cited publications, document types, publication by source titles, publication by institution. Next, intellectual interactions illustrated by co-authorships, and co-occurrence were also identified. One of the significant findings revealed that there was the slowly increased of flipped classroom publication and the decrease of citations. The findings presented in the study may be a caution for researchers to continuously maintain and boost publication productivity, and explore research methodologies that have been unexplored.